FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI YANG TERDAFTAR DI BEI PERIODE 2017 - 2018 - Heliani; Yulianti, Risma (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2020)
The pharmaceutical sector is a manufacturing company engaged in the health sector. This research was conducted to analyze whether profitability is influenced by the current ratio, debt ratio, sales growth and firm size using multiple linear regression analysis through SPSS. The population consists of 10 companies, namely pharmaceutical sector companies listed on the IDX for the 2017 - 2018 period. The use of a sample of 14 samples was determined by purposive sampling. Successful research shows that profitability is not influenced by the current ratio, debt ratio, sales growth and firm size.